Diferenças da imagem e tempo intensivo : percursos da virtualidade na filosofia de Gilles Deleuze - Guilherme Norton Andrade Silva (2020)
This dissertation aims to analyze virtuality as a way of being from which the operations of updating, differentiation and singularization prove to be indispensable for the determination of the event horizon that Gilles Deleuze's philosophy establishes. We organize our journey through three problematic axes that structure the chapters of the work: in the first, that of virtuality (in general), it was up to us to study this way of being and its fundamental operations, in particular, the pre-subjective field of intensities, the Deleuzian twist of the Kantian transcendental field, the relationship between the virtual, the actual, the possible and the real, as four modes of being. These themes proved to be fundamental for the need to bring consistency to the operations of virtuality, especially in the context of the 1960s. In the second axis, we deal with the relationship between virtuality and image, approaching this concept in Difference and Repetition and in works on cinema. From the Deleuzian reading of Bergson's philosophy, we analyze the developments that the notion of image suffers, in favor of the cinematographic readings that the author elaborated in the 1980s, with his concepts of "image-movement" and "image-time". In the third axis, it was up to us to investigate the problem of time in Deleuze's philosophy, highlighting the implications of the designation proposed by Deleuze, both in records from the 1960s and in works on cinema, about a “time in a pure state”. Finally, the problem of time and the aporias that involve its concept in the order of an intensive multiplicity, added to the aforementioned cinematographic concepts that Deleuze elaborates, made it possible to think about the experimentation itself of the virtual, latent and pre-subjective plane, which insists on clippings and objects thematized by Deleuze.